CTNI-21. TROTABRESIB (CC-90010) IN COMBINATION WITH CONCOMITANT TEMOZOLOMIDE PLUS RADIOTHERAPY AND ADJUVANT TEMOZOLOMIDE IN PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA: UPDATED RESULTS FROM A PHASE 1B/2 STUDY. (14th November 2022) - Vieito, Maria; Sepulveda, Juan Manuel; Moreno, Victor; de Vos, Filip; Geurts, Marjolein; Lorenzi, Elena; Macchini, Marina; van den Bent, Martin; Del Conte, Gianluca; Martín-Soberón, Maria Cruz; Brandal, Petter; Garcia, Maria Martinez; et al.
Abstract: Trotabresib, a novel bromodomain and extraterminal protein inhibitor, has demonstrated antitumor activity and blood–brain barrier penetration in patients with high-grade gliomas, and enhanced the antiproliferative effects of temozolomide in preclinical models. CC-90010-GBM-002 (NCT04324840) is a phase 1b/2 study investigating the addition of trotabresib to standard-of-care (SOC) concomitant temozolomide plus radiotherapy and adjuvant temozolomide, followed by maintenance trotabresib, in patients with newly diagnosed glioblastoma. The design of the dose escalation (part A) has been described previously (Vieito M, et al. SNO 2021. Abstract CTNI-51). Primary objectives of part A were to establish the safety, tolerability, and maximum tolerated dose/recommended phase 2 dose (RP2D) of trotabresib. In part A, addition of trotabresib to SOC was safe and well tolerated in the concomitant (N = 14) and adjuvant (N = 18) cohorts; the most frequent grade 3/4 treatment-related adverse event was thrombocytopenia (7/14 and 9/18 patients, respectively). The RP2D for trotabresib was 30 mg/day 4 days on/24 days off in both settings. At data cutoff (February 20, 2022), median duration of treatment was 34 weeks (concomitant cohort) and 33 weeks (adjuvant cohort); progression-free survival data are not yet mature. Trotabresib plasma pharmacokinetics and pharmacodynamics were consistent with monotherapy. At last follow-up, 6 and 5 patients remained on treatment in the concomitant and adjuvant dose-escalation cohorts, respectively, including 1 patient in cycle 20 with ongoing complete response. The ongoing randomized phase 2 dose expansion (part B; planned N = 162) is comparing concomitant trotabresib at the RP2D + SOC followed by adjuvant trotabresib at the RP2D + SOC, followed by maintenance trotabresib 45 mg/day 4 days on/24 days off, versus SOC alone in patients with newly diagnosed IDH –wild-type glioblastoma. Key objectives are to compare progression-free and overall survival, safety, and tolerability. Longer follow-up from part A and the first disclosure of data from part B will be presented.